Nanoparticles target early-stage breast cancer metastasis in vivo. (2nd October 2017) - Goldman, Evgeniya; Zinger, Assaf; da Silva, Dana; Yaari, Zvi; Kajal, Ashima; Vardi-Oknin, Dikla; Goldfeder, Mor; Schroeder, Josh E.; Shainsky-Roitman, Janna; Hershkovitz, Dov; Schroeder, Avi
Abstract: Despite advances in cancer therapy, treating cancer after it has metastasized remains an unmet clinical challenge. In this study we demonstrate that 100 nm liposomes target triple-negative murine breast-cancer metastases post intravenous administration. Metastatic breast cancer was induced in BALB/c mice either experimentally, by a tail vein injection of 4T1 cells, or spontaneously, after implanting a primary tumor xenograft. To track their biodistribution in vivo the liposomes were labeled with multi-modal diagnostic agents, including indocyanine green and rhodamine for whole-animal fluorescent imaging, gadolinium for magnetic resonance imaging (MRI), and europium for a quantitative biodistribution analysis. The accumulation of liposomes in the metastases peaked at 24 h post the intravenous administration, similar to the time they peaked in the primary tumor. The efficiency of liposomal targeting to the metastatic tissue exceeded that of a non-liposomal agent by 4.5-fold. Liposomes were detected at very early stages in the metastatic progression, including metastatic lesions smaller than 2 mm in diameter. Surprisingly, while nanoparticles target breast cancer metastasis, they may also be found in elevated levels in the pre-metastatic niche, several days before metastases are visualized by MRI or histologically in the tissue. This study highlights the promise of diagnostic and therapeutic nanoparticles for treating metastatic cancer, possibly even for preventing the onset of the metastatic dissemination by targeting the pre-metastatic niche.